Bilateral Distal Radius Fractures in a 12-Year-Old Boy after Household Electrical Shock: Case Report and Literature Summary - Norman Stone; Mara Karamitopoulos; David Edelstein; Jenifer Hashem; James Tucci (Case Reports in Medicine)
Background. Fracture resulting from household electric shock is uncommon. When it occurs, it is usually the result of a fall; however, electricity itself can cause sufficient tetany to produce a fracture. We present the case of bilateral fractures of the distal radii of a 12-year-old boy which were sustained after accidental shock. The literature regarding fractures after domestic electric shock is also reviewed. Methods. An Ovid-Medline search was conducted. The resultant articles and their bibliographies were surveyed for cases describing fractures resulting from a typical household-level voltage (110–220 V, 50–60 Hertz) and not a fall after the shock. Twenty-one articles describing 22 patients were identified. Results. Twenty-two cases were identified. Thirteen were unilateral injuries; 9 were bilateral. Proximal humerus fractures were most frequent (8 cases), followed by scapula fractures (7 cases), forearm fractures (4 cases), femoral neck fractures (2 cases), and vertebral body fracture (1 case). Eight of the 22 cases were diagnosed days to weeks after the injury. Conclusions. Fracture after electric shock is uncommon. It should be suspected in patients with persistent pain, particularly in the shoulder or forearm area. Distal radius fractures that occur during electrocution are likely due to tetany.